2023
DOI: 10.1007/s11357-023-00758-w
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic proteomics identifies targeted changes in liver metabolism and the ribo-interactome by dietary sulfur amino acid restriction

Abstract: Dietary sulfur amino acid restriction (SAAR) protects against diet-induced obesity, extends healthspan, and coincides with an overall reduction in hepatic protein synthesis. To explore the underpinnings of SAAR-induced slowed growth and its impact on liver metabolism and proteostasis, we resolved changes in hepatic mRNA and protein abundances and compared synthesis rates of individual liver proteins. To achieve this, adult male mice were provided deuterium-labeled drinking water while freely consuming either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Furthermore, GAGE analyses revealed that SAAR was associated with a seemingly paradoxical regulation of GO terms: SAAR was associated with upregulated cytoplasmic translation, but decreased transcription regulation complex, both of which are implicated in protein synthesis. In animals, SAAR slows overall protein synthesis 50 , but a recent publication outlines a complicated and dynamic machinery in which ribosomal proteins may be both upregulated and downregulated, possibly reflecting a shift in metabolic processes during SAAR 51 . However, these processes were studied in animal livers, and does not necessarily reflect processes in human WAT.…”
Section: Saar and Wat Gene Expressionmentioning
confidence: 99%
“…Furthermore, GAGE analyses revealed that SAAR was associated with a seemingly paradoxical regulation of GO terms: SAAR was associated with upregulated cytoplasmic translation, but decreased transcription regulation complex, both of which are implicated in protein synthesis. In animals, SAAR slows overall protein synthesis 50 , but a recent publication outlines a complicated and dynamic machinery in which ribosomal proteins may be both upregulated and downregulated, possibly reflecting a shift in metabolic processes during SAAR 51 . However, these processes were studied in animal livers, and does not necessarily reflect processes in human WAT.…”
Section: Saar and Wat Gene Expressionmentioning
confidence: 99%